Dating Violence in Relation to Problem Drinking and Risky Sexual Behaviors - Fernández, Aitor Sendino (International e-journal of criminal sciences, 2013)
This research studied the associations between dating violence (perpetration & victimization), problem drinking and risky sexual behaviors. A correlation analysis was carried out using a representative sample of the young adult population (18 to 27 years old) of the United States, obtained in the named as Add Health study. This analysis was conducted separately for men and women. Participants reported on the frequency of victimization or perpetration of physical, sexual or verbal violence on their intimate partners during the last year, as well as about their alcohol consumption-related consequences during the same period of time. They also answered to questions regarding their age of sexual initiation, number of sexual partners, use of birth control methods and condom use consistency during the last year. Correlations among most of the variables of study resulted positive and significant, with some gender differences emerging. The level of consistency of these results with the literature on the topic is examined, and future lines of research are proposed for a better understanding of the relationship between these variables.